Super Guinea Pig to the rescue - Weigelt, Udo.; Spranger, Nina (New York : Walker : Distributed to the trade by Holtzbrinck Publishers, 2007)
A guinea pig gets upset when his fellow pets make fun of his favorite television superhero, and so he makes a costume and pretends to be Super Guinea Pig himself.
Originally published in German as: Wundermeerschwein rettet die Welt. Düsseldorf : Patmos Verlag, 2006.
Mode of access: Internet.
Keywords: Friendship -- Fiction; Pets -- Fiction; Heroes -- Fiction; Friendship -- Juvenile fiction; Pets -- Juvenile fiction; Heroes -- Juvenile fiction; Picture books for children